Surgical Treatment of Primary Intracardiac Myxoma: 20-Year Experience in “Shahid Modarres Hospital”—A Tertiary University Hospital—Tehran, Iran - Zahra Ansari Aval; Hamid Ghaderi; Hassan Tatari; Mahnoosh Foroughi; Seyedeh Adeleh Mirjafari; Mohammad Forozeshfard; Kamal Fani; Isa Khaheshi (The Scientific World Journal)
Although cardiac tumors are not common they may vary in terms of race and surgical approach in different countries. Method. Patients data of 20 years was collected and evaluated in the “Shahid Modarres Hospital”—a tertiary university hospital—Tehran, Iran. Results. 42 patients with cardiac myxoma (all cases in 20 years) were included in study, 17 males and 25 females, age difference: 13 to 76 years (mean 50.6). Most of patients were in functional classes I, II. 35 patients complained of dyspnea and 3 patients had embolic events. 97.6% of tumors were primary (41 patients) and one tumor was recurrent (2.4%), 85.7% of tumors (36 cases) were located in LA, and 88.1% of tumors (37 cases) were pediculated. 40 patients (95%) had one tumor. In 22 patients (52.3%) after tumor resection septal defects were repaired primarily while in 18 patients (42.8%) the defects were repaired with pericardial patch and In one patient, tumor resected without any septal defect. Mean tumor size was about 5.22 cm (range of 2.2 to 8.2 cm). Postoperatively, 33 patients discharged from hospital without any complication. Discussion. The research reveals that patients’ age and gender were similar to that of other studies in other countries while tumor’s incidence seems to be higher. 3 patients were diagnosed after remote embolic event and one patient was diagnosed after MI reflecting relatively high tumor complications and late diagnosis. Conclusion. In our study mean time from diagnosis to operation was too long. The patients had more preoperative embolic events and complication. However, size of myxoma and location of that was as same as its rate in the other literature. As recommendation we suggested that in all patients with vague chest pain or remote embolic events cardiac myxomas should be ruled out.